Integrating sustainability in the design process of urban service robots - van der Schoor, Michel Joop; Göhlich, Dietmar (Frontiers in Robotics and AI, 2023)
The concept of sustainability and sustainable development has been well discussed and was subject to many conferences of the EU and UN resulting in agendas, goals and resolutions. Yet, literature shows that the three dimensions of sustainability (ecologic, social and economic) are unevenly accounted for in the design of mechatronic products. The stated reasons range from a lack or inapplicability of tools for integration into the design process, models for simulation and impact analyses to necessary changes of policy and social behavior. The influence designers have on the sustainability of a product, lies mostly in the early design phases of the development process, such as requirements engineering and concept evaluation. Currently, these concepts emerge mostly from performance-based requirements rather than sustainabilityimpact-based requirements, which is also true for service robots in urban environments. So far, the main focus of research in this innovative and growing product branch lies on performance in perception, navigation and interaction. This paper sets its focus on integrating all three dimensions of sustainability into the design process. Therefore, we describe the development of an urban service robot supporting the municipal waste management in the city of Berlin. It is the set goal for the robot, to increase the service and support the employees, while reducing emissions. For that, we make use of a product development process (PDP) and its adaptable nature to build a specific development process suited to include the three dimensions of sustainability during the requirements engineering and evaluation activities. Herein, we show how established design methods like the life cycle assessment (LCA) or life cycle costing (LCC) can be applied to the development of urban service robots and which aspects are underrepresented. Especially, the social dimension required us to look beyond standardized methods in the field of mechanical engineering. Based on our findings, we introduce a new activity to the development process that we call preliminary social assessment (PSA) in order to incorporate social aspects in the early design phase.